56+28x=

Simple and best practice solution for 56+28x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 56+28x= equation:


Simplifying
56 + 28x = 0

Solving
56 + 28x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-56' to each side of the equation.
56 + -56 + 28x = 0 + -56

Combine like terms: 56 + -56 = 0
0 + 28x = 0 + -56
28x = 0 + -56

Combine like terms: 0 + -56 = -56
28x = -56

Divide each side by '28'.
x = -2

Simplifying
x = -2

See similar equations:

| 16-4b=2(8-2b) | | 6*6-(7+5)= | | 3x^2+5x=11 | | -9=27-11p-13b | | 17=-2w-5 | | wz+5xy=8v | | 5-8abs(-2n)=-75 | | 7(q-3)=7q-3 | | -2+3p=-29 | | 5x-(9x+2)=-10 | | -6h-14+5h=h+14 | | 6(10+20)=180 | | 16a-10=3a+17 | | x+x-3+x+8+x-5=360 | | 7x-3x=10.2 | | 5x-(3x-6)=22 | | 7x+1=126 | | 6x^3=200 | | 8(2)+n=31 | | 1.4x+13.32=2.35x+21.92 | | (x-9)/7=3x | | 3-4(2x+7)=23 | | 10b-8=12b-10 | | 4(4/2+4)= | | 87+98+90+85=x | | -4(5x+2)=52 | | 8x+4(-4x+7)=34-8x | | x-9/7=3x | | x=43+86+51 | | 13m-21=9m-6 | | 7(2x-3)-3(5x+6)=-4(-3x+5)+5(-4x+5) | | 12-7b=18-9b |

Equations solver categories